Intrauterine growth and survival in cerebral palsy. Issue 2 (12th September 2007) - Hemming, K; Hutton, J L; Bonellie, S; Kurinczuk, J J
Abstract : Background and objectives: Deviations in birth weight from an optimum, thought to be just above average for gestational age, are known to increase both the risk of developing cerebral palsy and the risk of developing cerebral palsy of a more severe form. Influences on survival of such deviations from average birth weight for gestational age are not known. Methods: Using a well-established, well-defined and large UK cohort of children and adults with cerebral palsy, followed from birth for nearly 25 years, we investigate the influence of deviations from average birth weight for gestational age, on survival duration, after allowing for severity of impairments. Results: A total of 3946 cases, born between 1980 and 1996 were included. For those born much lighter than average for gestational age, more than 30% (n = 313) had a severe motor or cognitive impairment, rising to as much as 40% (n = 239) for extremely low weights. For female infants, the proportions severely impaired increased to as much as 35% (n = 49) among those born much heavier than average; no such increase was observed for heavier than average male infants. For those with four severe impairments and a birth weight close to average for gestational age, around 60% (n = 140) survived to age 15 years, compared with less than 40% (n = 9) of those born much heavier than average for gestational age. A 2-year-old child with four severe impairments and born heavy for gestational age has a predicted median life expectancy of 79% (95% CI 70% to 88%) of the average. Conclusions: Infants with a birth weight lighter than average for gestational age have an increased likelihood of developing a more severe form of cerebral palsy. Surprisingly, among the infants who are very severely impaired, those born much lighter than average for gestational age have the longest life expectancy, and those born much heavier than average for gestational age have the shortest life expectancy.